Pekerja migran Malaysia asal Kerinci Jambi dan pendidikan anak-anak mereka - Musli Musli; Della Amrina Yusra; Yumasdaleni Yumasdaleni (Jurnal Kependudukan Indonesia, 2022)
The existence of the name Kerinchi village in Kuala Lumpur is a trace of the migration of Kerinci residents to Malaysia. The increase in Indonesian migrant workers was parallel to the increase in the Malaysian economy in the 1990s that continues to this day. Although bringing children to settle in Malaysia is not allowed, the practise of bringing children illegally can be found. The study investigated the migration process of Kerinci residents and the education of their children. Data were collected using a qualitative method in Selangor, Malaysia and Danau Kerinci District (Jambi) in 2019 and 2021. The migration process is explained through four main factors, namely (1) lack of job opportunities in area of origin, (2) a higher value work and results in the destination area, (3) intention to have assets and continue children's education, and (4) social and family networks. Further, observations on the educational practises of the children who stay under illegal status show that they went to madrasah schools in the vicinity of PMI's residence because there are no document requirements, followed by returning back to Kerinci to take the Package A exam. Alternatively, migrant workers placed guardians over families with Malaysian citizenship status so that children born in Malaysia could attend formal schools. For the children who live in Kerinci, many of them go to university and some of them work in the formal sector. Migrating to become workers abroad is a form of effort to improve their children's education for Kerinci residents.